An empirical assessment of the Swedish Bullionist Controversy - Nils Herger (Swiss National Bank, Study Center Gerzensee, 2017)
In the eighteenth century, a fierce political debate broke out in Sweden about the causes of an extraordinary depreciation of its currency. More specifically, the deteriorating value of the Swedish daler was discretionarily blamed on monetary causes, e.g. the overissuing of banknotes, or nonmonetary causes, such as balance of payments deficits. This paper provides a comprehensive empirical assessment of this so-called "Swedish Bullionist Controversy". The results of vector autoregressions suggest that increasing amounts of paper money did give rise to inflation and a depreciation of the exchange rate. Conversely, nonmonetary factors were probably less important for these developments.
Keywords: B12; B17; E42; F31; N13; 330; bullionism; floating exchange rate; inconvertible banknotes; paper currency; Sweden